Comparative Analysis and Characterisation of Amine-Local Solvent Blends for Natural Gas Sweetening - Tare Caroline Gillow; Ipeghan J. Otaraku; Peter O. Muwarure; Johnson Nnadikwe; Onuche Izuchukwu (SEAN Institute, 2025)
This study compared and characterised hybrid amine-local solvent blends for sustainable natural gas sweetening. The study designed and evaluated an absorption process using blends of monoethanolamine (MEA) with solvents derived from agricultural waste Plantain Peel Ash Extract (PPAE) and Coconut Shell Ash Extract (CSAE). The comprehensive characterisationprovided fundamental insights into the viability of using agricultural waste for gas sweetening. Plantain peels' high volatile matter (74.3%) yields ash rich in active alkaline compounds during calcination, while coconut shells' higher fixed carbon (19.5%) produces more stable char with lower alkaline content. The ultimate analysis showed that coconut shells' higher carbon content (49.5%) aligns with its lignocellulosic nature, while plantain peels' higher oxygen content (47.5%) indicates more carbohydrate-rich material that decomposes to yield higher ash alkalinity.The electrolyte properties further confirm PPAE's superiority, with higher pH (12.1), conductivity (28.5 mS/cm), and ionic strength (0.42 mol/L), all contributing to better absorption performance while influencing corrosion behavior.